Setting up and running a small-scale business producing high-value foods - Axtell, Barrie; Fellows, Peter (Technical Centre for Agricultural and Rural Cooperation, 2014)
Whether you want to start a new business, or improve or diversify an existing operation, this unique text collects for the first time essential information on the demand for high-value foods, their production, marketing and quality management. Aiming to raise awareness of opportunities in high-value foods and ingredients in ACP countries, the handbook also highlights routes to access different types of value chains for these products. Clearly laid out, with helpful summaries and ‘tips for success’, this comprehensive publication presents numerous real-life case studies to inspire entrepreneurs to improve their production and profitability.